Practicing Democracy from Childhood: Democratic Praxis in Te Ao Māori - Smyth K; Napan K; Perkins R; Hunter R (Berghahn Books)
Democracy manifests itself in a range of ways and is an imperfect, dynamic struggle for collective decision-making. This article discusses the multifaceted processes of deliberative democratic praxis found in traditional Māori society. Central to decision-making in te ao Māori, hui provide formal and informal structures for deliberative democracy, precedent setting, learning, and transformation through consensus making, inclusive debate, and discussion across all levels of society. Rather than coercion and voting, rangatira relied on a complex mix of customary values and accomplished oratory skills to explore issues in family and community meetings and in public assemblies. Decisions made through inclusive deliberative processes practiced in hui established evident reasoning and responsibility for all community members to uphold the reached consensus. This article claims that practicing deliberative democracy as a fundamental way of life, learned through ongoing active and meaningful participation throughout childhood, improves the integrity of democratic decision-making.
Keywords: consensus; deliberative democracy; democratic schooling; hui; indigenous; Māori; 1606 Political Science